Envolvimento dos canais de potássio na ação espasmolítica do ácido 8(17), 12E, 14-labdatrieno-18-óico (labdano-302), isolado de Xylopia langsdorfiana A. St.-Hil. & Tul. em íleo isolado de cobaia - Macêdo, Cibério Landim (2008)
8(17),12e,14-labdatrien-18 oic acid (labdane-302), is a diterpene isolated from the stem bark of Xylopia langsdorfiana A. St.-Hil. & Tul. In a preliminary study, Ribeiro (2003) demonstrated that labdane-302 inhibited the phasic contractions induced by carbachol (CCh) or histamine (IC50 = 1.7  0.5 and 0.9  0.2 x 10-5 M, respectively) on guinea-pig ileum. The aim of the present study was to investigate the spasmolytic action mechanism of labdane-302 in that organ. Isometric and isotonic contractions were monitored, and the parameters of relative potency and efficacy were determined from cumulative concentration-response curves. Labdane-302 inhibited (pD´2 = 4.9  0.2; r2 = 0.8  0.1) the cumulative concentration-response curves to histamine, and these were shifted to the right, in a non-parallel manner (Schild plot slope = 4.2  1.4), with depression of the maximal effect (Emax), suggesting a noncompetitive antagonism. Labdane-302 relaxed, in an equipotent manner, the ileum pre-contracted with KCl, CCh or histamine, suggesting that this diterpene could be acting on Cav. This assumption was confirmed by observation that labdane-302 antagonized the CaCl2 induced contractions in the depolarizing medium without Ca2+ (pD´2 = 5.3  0.1; r2 = 0.5  0.05 ), with shift of the concentration-response curve to the right, in a non-parallel manner (Schild plot slope = 2.6  0.5), with depression of Emax. As in the guinea-pig ileum the major CaV subtype is the Cav 1, we decided to investigated its role in the action mechanism of labdane-302, and was verified that the diterpene relaxed (EC50 = 3.6  0.8 x 10-5 M) the ileum pre-contracted with S-(-)-Bay K8644, a selective agonist of the Cav1. As the potent relaxing of labdane-302 was no different when ileum pre-contracted with KCl or S-(-)-Bay K8644, it is suggestive of indirect blockade of the Cav1. Since K+ channels play a major role in the regulation of membrane potential and modulation of CaV, we decided to investigate the participation of K+ channels in the spasmolytic action of labdane-302. The relaxant potency of labdane-302 (EC50 = 1.5  0.3 x 10-5 M) was decreased on 2.4 times in the presence of CsCl, a non-selective K+channels blocker (CE50 = 3,5  0,6 x 10-5 M), suggesting a possible involvement of the K+ channels in the spasmolytic effect caused by labdane-302. In order to verify which subtypes of K+ channels could be involved we used selectives blockers of these channels. The observation that 4-aminopyridine, a selective blocker of Kv, and that TEA+ 1 mM, a selective blocker of the BKca did not change the relaxant effect of labdane-302 suggests that KV and BKca are not involved in its action mechanism. On the other hand, the log concentration-response curve induced by labdane-302 was shifted to the right in the presence of apamine, selective blocker of the SKCa, (EC50 = 3.3  0.4 x 10-5 M) or glibenclamide, selective blocker of the KATP, (EC50 = 3.2  0.3 x 10-5 M), suggesting the involvement of SKCa and KATP in the spasmolytic action mechanism induced by labdane-302 on guinea-pig ileum. In the presence of aminophylline the potency of labdane-302 was increased (EC50 = 0.4 ± 0.03 x 10-5 M), which indicate participation of cyclic nucleotides. These results suggest that the relaxant effect of labdane-302 on guinea-pig ileum, involves the activation of the SKCa and KATP with the consequent blocking of Cav-L and involvement of the cyclic nucleotides.